PLAN DE MARKETING PARA LOS ATRACTIVOS TURÍSTICOS DE LA PARROQUIA JIMBURA DEL CANTÓN ESPÍNDOLA DE LA PROVINCIA DE LOJA - Pérez Andrade, Fernando Patricio (2016)
The "Marketing plan of the Touristic Attractions of Canton Espíndola parish Jimbura in the province of Loja" has been a topic chosen based on its unique tourist attractions in the province of Loja; and what is intended with the development of this work is to promote them and make them known under certain limits and parameters that contribute to the good life of local people and conservation of the environment. This project focuses on the lack of development and tourism promotion that exists in the rural parish of the canton Jimbura Espíndola, as the authorities of the Autonomous Decentralized Government Jimbura, do not care to promote the different attractions that owns the Parish. Jimbura is located south of Canton Espíndola belonging to the Province of Loja, This heavenly place is very crowded by the beauty of the natural lakes because they are formed on volcanic rocks, located 23 km from Amaluza (regional town) the whole lake is formed by three gaps of about 15 hectares, at 3390 msnm where nature stands out in all its splendor, tourists are attracted by all the stunning scenery of this site that has become the destination not to admire all components. In the parish previously have conducted studies to characterize the current situation of interest why was the need to create a base thereof to serve as a starting point for developing a marketing plan to provide online at tourism development in the parish. With this background the importance of this research, which is titled " MARKETING PLAN FOR TOURIST ATTRACTIONS JIMBURA PARISH OF CANTON ESPÍNDOLA Loja province," the same that was fulfilled as a prerequisite to obtaining denoted Engineering degree in tourism Administration, National University of Loja, and this is intended to give a contribution to tourism development in the parish of Canton Espíndola Jimbura. The overall objective of this work was to develop a marketing plan for attractions Jimbura Parish, to contribute to the economic development of the parish and promote it as a tourist destination, generating income through appropriate dissemination of tourist attractions own, seeking the means and resources needed for implementation. The specific objectives of this study were to conduct an assessment of the current situation of attractions Jimbura, Canton Espíndola parish; Designing the proposed Marketing for attractions Jimbura parish; Socialize and finally the proposal of Marketing at the Autonomous Decentralized Government Jimbura Parish, Canton Espíndola province of Loja. 5 The methodology was framed by the reality of each of the specific objectives; therefore the research, scientific, bibliographic, analytical method, were necessary at the time of collecting field data and bibliographic information, consequently they proceeded to gather the information through the application of chip inventory attraction was considered essential to capture the tourist services, survey analysis and FODA analysis. That allowed us to know the strengths, opportunities. Weaknesses and threats the tourist area of the parish. To obtain truthful results survey was applied to the inhabitants of Canton Espíndola in order to know the current situation of tourism and tourism development alternatives for Jimbura parish. Due to the above we can conclude that the Jimbura parish should be promoted for tourism, this is due prior to adapt the infrastructure, training people involved in tourism services and the people of the parish. The interests taken into account in this marketing plan are exploited to generate jobs and revenue for the parish, thus converting to tourism in one of the areas of greatest economic benefit of the Parish. Achieving achieve adequate competition from other tourist destinations of the province of loja